2020
DOI: 10.1021/acsami.9b23098
|View full text |Cite
|
Sign up to set email alerts
|

An Integrating Platform of Ratiometric Fluorescent Adsorbent for Unconventional Real-Time Removing and Monitoring of Copper Ions

Abstract: Nondegradable heavy metals have caused great dangers to the environment and human health. Combining stimuli-responsive materials with conventional MOF-based adsorbents has been considered an effective method to generate intelligent adsorbents for superior control over the adsorption process. Herein, a smart MOF-based ratiometric fluorescent adsorbent was designed to accurately monitor the progression of the removal of copper ions with dual-emitting fluorescence signal. Unlike the traditional difunctional mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…SPBI-c (28.5% alkylation) and SPBI-g (65.0% alkylation) could also discern Cu 2+ and Fe 3+ but with different sensitivities (Figures S27-S39 and further discussions can be seen in the SI). The signals of SPBI-c were more sensitive to Cu 2+ than those of SPBI-g, and its sensitivity was also better than those of some reported metal ion sensors (Table S6) (Kim et al, 2013;Zhang et al, 2020a;Du et al, 2020). For Fe 3+ , the sensitivity of SPBI-c was also higher than that of SPBI-g as well as those of some reported Fe 3+ sensors (Table S7) (Li et al, 2019a(Li et al, , 2019bFan et al, 2020;Cui et al, 2020;Zheng et al, 2020;Shia et al, 2020;Jia et al, 2020;Sun et al, 2020).…”
Section: Sensing Performance Of Spbis Toward Metal Ionsmentioning
confidence: 82%
“…SPBI-c (28.5% alkylation) and SPBI-g (65.0% alkylation) could also discern Cu 2+ and Fe 3+ but with different sensitivities (Figures S27-S39 and further discussions can be seen in the SI). The signals of SPBI-c were more sensitive to Cu 2+ than those of SPBI-g, and its sensitivity was also better than those of some reported metal ion sensors (Table S6) (Kim et al, 2013;Zhang et al, 2020a;Du et al, 2020). For Fe 3+ , the sensitivity of SPBI-c was also higher than that of SPBI-g as well as those of some reported Fe 3+ sensors (Table S7) (Li et al, 2019a(Li et al, , 2019bFan et al, 2020;Cui et al, 2020;Zheng et al, 2020;Shia et al, 2020;Jia et al, 2020;Sun et al, 2020).…”
Section: Sensing Performance Of Spbis Toward Metal Ionsmentioning
confidence: 82%
“…According to the calculation method reported in the literature [ 47 , 48 , 49 ], the fluorescence detection limit of sensor CPBI 2 for Cu 2+ and Zn 2+ can be calculated as 5.98 × 10 −9 M and 6.02 × 10 −9 M, respectively ( Figure 5 b,d). Compared with the data reported before, the results indicate that sensor CPBI 2 is more sensitive than most known Cu 2+ and Zn 2+ sensors [ 50 , 51 , 52 , 53 , 54 ] (more comparisons can be seen in Tables S5 and S6 ).…”
Section: Resultsmentioning
confidence: 56%
“…According to the calculation method reported in the literature [47][48][49], the fluorescence detection limit of sensor CPBI 2 for Cu 2+ and Zn 2+ can be calculated as 5.98 × 10 −9 M and 6.02 × 10 −9 M, respectively (Figure 5b,d). Compared with the data reported before, the results indicate that sensor CPBI 2 is more sensitive than most known Cu 2+ and Zn 2+ sensors [50][51][52][53][54] (more comparisons can be seen in Tables S5 and S6). In addition, as a "turn-off" fluorescence sensor, the fluorescence-quenching proces of CPBI2 can be determined by Stern-Volmer (S-V) constant (Ksv), whose calculation formula is: I0/I = 1+Ksv[Q] (Figure 6).…”
Section: Sensing Performance Of Cpbi N Towards Metal Ionsmentioning
confidence: 58%
“…Zhou and Wang et al reported a ratiometric luminescent RhB@ZIF-8, which was prepared through encapsulating dye molecule Rhodamine B (RhB) into ZIF-8. [75] ): Compared with the above mentioned heavy metal ions, Cr(VI) species, as toxic anions, is more widely detected using LMOF-based sensors. Our group reported a 3D heterometallic Dy-Zn MOF by 4,4′-dicarboxylate-2,2′-dipyridine anion ligand.…”
Section: Heavy Metal Ionsmentioning
confidence: 99%